Spatial characteristics and cultural factors of Yi nationality traditional dwellings based on spatial syntax - Lai, Qin; Liu, Wei; Li, Xing; Jin, Qiu (Frontiers in Earth Science, 2023)
The spatial layout of traditional residential houses is closely related to national and regional characteristics and culture. The traditional village of Yi nationality is selected, and the organization structure of the outside village and the inside living space is studied through the graphical and quantitative analysis method of space syntax. The primary purpose of this study is to analyze the spatial characteristics of Yi dwellings and infer the cultural factors behind them. To explore how to integrate traditional spatial characteristics into contemporary design and promote the preservation and inheritance of architectural culture. The results show that (1) the outer village space of residential houses is characterized by weak identifiability, compact and loose organizational structure, weak permeability, and weak accessibility; (2) The interior space of dwellings presents a spatial layout with the main room and courtyard as the core as a whole. The interior space of dwellings is abundant and flexible, and the accessibility of ancillary functional space is weak. (3) The cultural causes of the formation of these spatial features include complex landforms, family systems, hierarchical systems, semi-agricultural and semi-pastoral production modes, the concept of valuing family harmony, the use of regional materials, respect for nature, fire worship, etc. (4) The spatial characteristics of traditional dwellings are inherited in contemporary dwellings. Fuzzy elements can be added in villages according to family relations, and characteristic Spaces such as courtyards and fire ponds in traditional dwellings can be preserved.